The Rise of AI in Business: Uncharted Avenues for Digital Transformation - Mardani, Agnes Dini (Universitas Tanjungpura, 2024)
This study investigates the transformative impact of Artificial Intelligence (AI) on PT. Perhutani Anugerah Kimia, with a focus on user experience, AI investments, digital transformation, and their collective influence on increased business efficiency. Through path analysis, the study reveals statistically significant direct effects, highlighting the pivotal role of user experience and strategic AI investments in propelling digital transformation and, consequently, improving business efficiency. The indirect effects analysis underscores the mediating role of digital transformation, elucidating how enhancements in user experience and AI investments positively cascade to boost business efficiency. These findings advocate for a strategic emphasis on user-centric approaches and substantial AI investments, positioning organizations to navigate the evolving business landscape by fostering digital transformation and realizing tangible operational efficiency gains. This research contributes valuable insights to organizations seeking to harness the full potential of AI for holistic and impactful digital evolution.